An Easy-to-Fabricate Radially Polarized Surface-Emitting Single-Mode Laser - Xiang Ma; Quanan Chen; Ye Liu; Qiaoyin Lu; Weihua Guo (IEEE Photonics Journal)
A new design of radially polarized surface-emitting laser (RPSEL) is presented for the first time. RPSEL which has a second-order grating shallowly etched on top of a microcylinder cavity is easy to fabricate. The grating selects a specific whispering-gallery mode with the proper emission pattern (radially polarized emission) to lase and simultaneously scatters the mode vertically to form the surface emission. Through numerical simulations, RPSEL is predicted to be a single-mode laser with radially polarized surface emission. RPSEL can be rather easily realized at different wavelengths such as the near infrared 1310 and 1550 nm wavelength bands. Furthermore, it can be fabricated with microcylinder cavities with very small radii even down to wavelength-scale, therefore it has the potential to realize very high modulation bandwidth and very low threshold current.